EXPLORING ONLINE RESERVATION DECISION THROUGH E-COMMERCE PLATFORM IN THE HOTEL INDUSTRY - Tasmara, Dinda Alysa; Islami, Genzia Aurela Joya; Ferdian, Feri (Politeknik Bosowa, 2024)
E-Commerce currently has a very high growth rate where the needs that are obtained quickly and precisely become the main target for the world of e-commerce, one of the industries that have started using e-commerce is the hospitality industry that utilizes this internet technology. With the e-commerce platform, people can make reservations online because there are many choices of hotels along with reviews, ratings and facilities that have been listed on the e-commerce platform and there are even discounts, promotions and prices that are cheaper than making walk-in reservations and discounts without having to go to the hotel they want to go to so they can save time, so they have considerations and decisions in making online reservations. The purpose of this study is to examine the effect of purchase information and assessment of promotional benefits on online reservation decisions through e-commerce platform in the hospitality industry. The methodology used to conduct this research is quantitative with a causal associative approach. The data was obtained by distributing questionnaires online through people who have used e-commerce platforms in making online reservations in the hotel industry, so that 150 people were obtained, with a Likert scale. The data analysis technique used the Partial Least Square Structural Equation Modeling. Most respondents were between 17-25 years old with 84% of respondents. The results found that purchasing information experience affects online reservation decisions in the hotel industry. Meanwhile, the assessment of promotion benefits does no effect online reservation decisions in the hotel industry. This study concludes that when people want to make an online reservation they will look at the ratings, evaluations, or comments given by individuals or users who have stayed and used services at the hotel and with the many discounts, promotions, price cuts and cheaper prices when making online reservations using e-commerce platforms will increase online reservation decisions in the hotel industry.